Use Of Social Media For Marketing Of Library And Information Services In Academic Libraries - Rajiv Kumar; Dr Jatinder Kumar (Educational Administration: Theory and Practice, 2024)
Academic libraries play a crucial role in facilitating the acquisition of knowledge and information for students in higher education. This study examines the utilization of social media platforms as a means of promoting academic libraries and enhancing their marketing effectiveness. Through the collection of primary quantitative data via a survey administered to 165 participants, the study explores the relationship between social media usage and library marketing strategies. Utilizing statistical analysis tools such as SPSS, the study interprets data pertaining to key variables including social media engagement and marketing approaches. The findings underscore the significance of leveraging social media platforms to amplify the visibility and utility of academic libraries, particularly in higher education settings. This research contributes to a deeper understanding of the evolving role of social media in modern library marketing practices and highlights opportunities for enhancing engagement and outreach within the academic community.